Murderous consent : on the accommodation of violent death - Crépon, M. (Marc), 1962- (Perspectives in continental philosophy., 2019)
Murderous Consent details our implication in violence that we do not directly inflict but in which we are structurally complicit. Marc Crépon invites the reader to resist that implication by arguing for an ethicosmopolitics grounded in our receptivity to the pleas for assistance that the vulnerability and mortality of the other enjoin everywhere.